Followers' Reception of Anies Baswedan's Image on the @pinterpolitik Social Media Account - Asrianto, Ikhsan Danar; Rochmaniah, Ainur (Fakultas Dakwah UIN Saizu Purwokerto, 2024)
Instagram has developed into a media tool in political dynamics. Political content on Instagram can build opinions for media audiences (followers) who access it, so followers become strategic targets for receiving political messages through constructed content. This study aims to describe the followers' reception of Anies Baswedan's image as a 2024 presidential candidate on the @pinterpolitik account. This research method uses a qualitative approach with an interpretative paradigm. Data analysis is used to conclude the reception of @pinterpolitik account followers. The data collection technique uses the in-depth interview method. Informants were selected based on the @pinterpolitik followers who are university students. Reception analysis is used to determine the implications of research subjects for messages in mass media. Stuart Hall's decoding and encoding theory divides followers' positions into three categories to find reception patterns: dominant-hegemonic, negotiation, and opposition. The results of this study show that informants who are followers are in a dominant hegemonic position in receiving information about Anies Baswedan on the @pinterpolitik account. This tendency to gather information from the account is based on their trust in the independence of the @pinterpolitik account in disseminating information. Moreover, every information disseminated has valid and accountable sources and data. Based on the assessment based on information on the @pinterpolitik account, Anies Baswedan's image is positively assessed as an intellectual individual, organized rhetoric, narrating according to data, and a religious individual.